Partisipasi Sosial-Politik sebagai Praktik Hospitalitas Kaum Pentakostal - Fransiskus Irwan Widjaja; Harls Evan R. Siahaan; Octavianus Nathanael (Sekolah Tinggi Teologi Intheos Surakarta, 2021)
Abstract. The involvement of the church in social life outside the church is something that continues to struggle from time to time; the church, on the one hand, felt compelled to be involved in all aspects of life; on the other, it felt sufficient to focus on the spiritual dimension of life. Meanwhile, participation in the social domain is often articulated with religious mission activities that wish to win souls and increase the number of church members. This article aimed to present a theological reflection framework on hospitality in a Pentecostal perspective, as a spirituality that drives the participatory philosophy of Pentecostals in the public sphere, both socially and politically. The method used is descriptive analysis, with a literature study approach. The result is that the hospitality attitude of the early church in the Acts constructs a Pentecostal reflection of the participation of Pentecostals in the public sphere.Abstrak. Keterlibatan gereja dalam kehidupan sosial di luar gereja merupakan hal yang terus mengalami pergumulan dari waktu ke waktu; gereja di satu sisi merasa harus terlibat dalam seluruh aspek kehidupan, di sisi lain merasa cukup untuk memfokuskan pada dimensi kehidupan rohani. Sementara itu, partisipasi pada domain sosial tidak jarang diartikulasikan dengan kegiatan misi gerejawi yang ingin memenangkan jiwa dan menambahkan jumlah anggota gereja. Artikel ini bertujuan menyajikan sebuah kerangka refleksi teologis tentang hospitalitas dalam perspektif Pentakostal, sebagai spirtualitas yang menggerakkan sikap partisipatif kaum Pentakostal pada ruang publik, baik secara sosial dan politik. Metode yang digunakan adalah analisis deskriptif, dengan pendekatan studi literatur. Hasilnya, sikap hospitalitas jemaat mula-mula pada narasi Kisah Para Rasul mengonstruksi sebuah perenungan Pentakostal mengenai partisipasi kaum Pentakostal pada ruang publik.